Agave obscura new record in the diet of nectarivorous bats Leptonycteris nivalis, Choeronycteris mexicana and Anoura geoffroyi in the mountains of central Veracruz, México - Galindo-González, Jorge; Cuéllar-Martínez, Manuel; Mac Swiney G., M. Cristina (Therya Notes, 2024)
We report the interaction of the nectarivorous bats Leptonycteris nivalis, Choeronycteris mexicana and Anoura geoffroyi with the flowers of Agave obscura Schiede (Asparagaceae). In this interaction we verified the consumption of nectar and pollination of A. obscura flowers, which is why we report for the first time A. obscura as part of the diet of these nectarivorous bats. Agave obscura is an endemic species of México with distribution in the states of Tamaulipas, San Luis Potosí, Veracruz, Puebla and Oaxaca. Through video recordings and analysis of pollen samples collected directly from the bats, we recorded the interactions between May and June 2018, in the mixed pine-oak forest of Toxtlacoaya, municipality of Las Vigas de Ramírez, Veracruz, México (2,426 m). Eighteen nectarivorous bats were captured: L. nivalis (n = 9), C. mexicana (n = 3) and A. geoffroyi (n = 6), foraging inflorescences of A. obscura, the bats presented agave pollen on their snouts, chest, head, or wing membranes. This is the first known record of the interaction of these bats with A. obscura, which adds conservation value to this endemic species as a food source for Mexican nectarivorous bats.